Les fondements sémantiques de la préférence pour 'manipuler' ou 'modifier' dans le contexte de la bioéthique - Cozma Ana-Maria; Lehtonen Kim (France, 2025)
This study aims to understand the semantic specificities of the French lexemes manipuler and modifier in order to shed light on their use in bioethics when they affect an embryo, the brain, DNA, human, what is alive, or procreation. Based on dictionary definitions and responses to a questionnaire submitted to French speakers, and using concepts from various approaches in semantics (combinatorial semantics, argumentative semantics, frame semantics and semantic aspect), the study identifies the meaning elements specific to the two lexemes. These elements are closely linked to the meaning potential of the lexemes and the aspectual features of the processes they designate. At the end of this study, a set of semantic features characteristic of each lexeme is proposed, from a contrastive perspective.